The Influence of Digital Competence and Work Motivation on Academic Service Quality - Sunyoto; Nunuk Hariyati; Ayu Wulandari; Amrozi Khamidi; Mohammad Syahidul Haq (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2026)
This study aims to examine the influence of digital competence of educational staff on academic service quality through the dual mediation of work motivation and performance at Campus 2 of State University of Surabaya(UNESA). The research employed a quantitative approach with a cross-sectional survey design involving 106 educational staff selected through purposive sampling and stratified random sampling. Data were collected using a structured questionnaire with 68 items measuring digital competence (DigCompEdu), work motivation (Herzberg's Theory), performance (IWPQ), and academic service quality (HEdPERF). Data analysis utilized Structural Equation Modeling (SEM) with IBM AMOS 24.0 and bootstrapping technique with 5000 resamples. Results revealed that digital competence significantly affects work motivation (β=0.453; p<0.001), performance (β=0.287; p<0.001), work motivation influences performance (β=0.394; p<0.001), and performance affects academic service quality (β=0.521; p<0.001). The dual mediation effect was significant with total indirect effect β=0.238 (p=0.002), and the model explains 67.4% of academic service quality variance. The novelty lies in integrating a comprehensive serial mediation model, demonstrating that digital competence transformation into academic service quality requires simultaneous psychological (motivation) and behavioral (performance) pathways within Indonesian higher education contexts. Digital competence improves the quality of academic services by strengthening work motivation and optimizing performance. These findings confirm that improving academic services in higher education requires an integrated strategy that combines digital competence development, motivational interventions, and systematic performance management.